2018
DOI: 10.1186/s13028-018-0401-9
|View full text |Cite
|
Sign up to set email alerts
|

Hock lesions in dairy cows in freestall herds: a cross-sectional study of prevalence and risk factors

Abstract: BackgroundHock lesions (HL) in dairy cows are a common animal welfare problem in modern dairy production with freestall housing systems, but there are no large-scale studies addressing its epidemiology in Sweden. The aims of this cross-sectional study were to investigate the prevalence of HL of different severity in 100 Swedish freestall dairy herds, and to identify cow- and herd-related risk factors. Associations between HL and mastitis as well as culling were also investigated.ResultsIn total, 3217 cows from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…This is particularly the case for milking-system-related risk factors. We only found one study 45 that linked herringbone milking parlors to a higher risk of hock lesion, a sign of lameness, than tandem parlors, which is consistent with our findings on lameness risk variables (see “ Supplement ”).…”
Section: Resultssupporting
confidence: 91%
“…This is particularly the case for milking-system-related risk factors. We only found one study 45 that linked herringbone milking parlors to a higher risk of hock lesion, a sign of lameness, than tandem parlors, which is consistent with our findings on lameness risk variables (see “ Supplement ”).…”
Section: Resultssupporting
confidence: 91%
“…Hock lesions are a common welfare problem on mattress-based stalls and their prevalence is high also in other Nordic countries, for example in Norway (prevalence of mild lesions 53%; Kielland et al 2009) and in Sweden (prevalence of mild lesions 68%; Ekman et al 2018). As in our study, others have reported that prevalence of integument alterations increases with increasing parity (Potterton et al 2011, Ekman et al 2018.…”
Section: Discussionsupporting
confidence: 79%
“…concrete, rubber matt or mattress) was used as an independent variable in their study. On the other hand, research using peat bedding reports that it reduces the risk for mild hock lesions compared to other common organic bedding materials, such as straw and sawdust (Ekman et al 2018). Regardless, it is evident that integument alterations have a high prevalence in mattress stalls, at least compared to deep-bedded stalls (Lombard et al 2010, Potterton et al 2011, and thus, it makes the comparison of our results to other published research challenging.…”
Section: Discussionmentioning
confidence: 61%
“…Although focused on hock lesions only, a recent study in Sweden also found higher odds of lesions when herringbone parlors were used compared with tandem parlors. This was believed to be due to the flow of cows through the parlor, as tandem parlors allowed for cows to enter and exit individually (Ekman et al, 2018). Although no tandem parlors were present in the current study, the flow of cattle through the parlor could be an important factor.…”
Section: Discussionmentioning
confidence: 74%